Behaviors and Effects of Smartphone Usage among High School Students, Nonthaburi Province - สุวรรณเจริญ, ศักดิกร; ธรรมาอินทร์, สุพัตรา; เกิดม่วง, สุวัฒนา; พินิจจันทร์, อังค์ริสา; ชุมชัย, พรเลิศ (Nursing Journal of The Ministry of Public Health, 2019)
Smartphone usage behavior of teenagers has both positive and negative effects on them, their families and society. The objectives this descriptive correlational research study aimed to study the behaviors and effects of smartphone usage and examine the relationship between smartphone usage behaviors and the impact of using the smartphone among high school students, Nonthaburi province. A total of 291 high school students in the selected school, Nonthaburi province, were selected by simple random sampling. The data was collected using self-administrated questionnaires. The data were analyzed using descriptive statistics and Pearson’s Correlation Coefficient. The results showed that the sample was female (79.70%). The average age was 16.80 years (SD=.97). The average smartphone service charge per month was 394.60 baht (SD=243.32). The time of playing smart phone was after school (81.80%), and most of them played at home, 97.30%. The sample had a behavior of using smart phones at a medium to high level of 98.60 percent. The impact of the use of smart phones was at low to moderate level among 268 students (92.10%). Classification of impacts on each aspect showed moderate level on health and psychological impacts. The relationship between smartphone usage behaviors and the effects of using the smartphone among high school students was statistically significant (p<.01). The results of the study can be used as a guideline for related parties to formulate policies or methods to adjust behaviors that are problematic in the use of smartphones and to prevent further long-term problems.